The effect of oil and coolant temperatures on diesel engine wear - 197678 Bolis, David A.; Johnson, John H.; Daavetilla, Donald A.; Society of Automotive Engineers (United States); International Automotive Engineering Congress and Exposition (1977: Detroit, MI) (Warrendale, Pa : SAE, 1977)
PSZJBL